APLIKASI PENGELOLAAN DATA LANSIA DAN DATA BALITA POSKESDES DESA TANJUNG HARAPAN BERBASIS WEBSITE - ningsih, irma yulia; Purnomo, Wulan Andang; Putra, Firmansyah (Universitas Multi Data Palembang, 2025)
The Village Health Post (Poskesdes) of Tanjung Harapan still manages elderly and toddler data manually using logbooks, which leads to several issues such as data inaccuracy, delayed reporting, and duplicated information. This study aims to design and develop a web-based application to support the efficient and accurate recording, processing, and reporting of elderly and toddler health data. The system development follows the Waterfall model, consisting of needs analysis, system design using UML (Unified Modeling Language), implementation, and testing using the Black Box method. The result of this research is a web-based information system featuring data management for elderly individuals, toddlers, immunizations, vitamins, and health reports, accessible by administrators and Poskesdes staff. The system is developed using PHP programming language and MySQL database. The implementation of this application is expected to enhance the effectiveness and efficiency of health services at the Tanjung Harapan Poskesdes and support the digitalization of community health data at the village level.